GAMBARAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEKAMBUHAN GASTRITIS - Yektiningsih, Erwin; Kurniyawan, Candra Bagus (Jurnal AKP, 2014)
Gasthritis is one of health problems that mostly disturb digestion tract. Most of gasthritis are caused by inappropriate dietary pattern, monotous dietary menu, unbalanced dietary menu, stress and low in keeping sanitation and consume medicines without prescription. Gathritis can cause death if there is complication on other digestion organs. The purpose of this research is to identify description of factors that influence gasthritis relapse at Region Technical Implementer Unit of Plosoklaten Public Health Center in Kediri Regency in 2014.Research design was descriptive. The Variable of this research is description of factors that influence gasthritis relapse and Instrument using a questionnaire. Population consisted of 55 people with sample size of 28 respondents. The sample was taken with accidental sampling technique. Data analysis in this research through the stages of editing, coding, scoring and tabulating with bar diagramFrom research result showed that stress factor 78,57%, dietary factor 63,39% and medicine factor 53,37%. It can be concluded that the most factors influence gasthritis relapse is stress factor. Psychology stress will increase simpatico nerve activity which can stimulate HCL production. Raising HCL was stimulated by chemistry mediator which outted by simpatico neuron like ephineprin so gastritis can relapse.To minimize gasthritis relapse which caused by stress factor, dietary factor and medicine factor, the role of nurse is for doing health program. The programs was applied health promotion with illumination or giving health education about gastritis disease in society. Keywords: factor of gasthritis relapse patients, gasthritis